A taxonomic review of the coastal genus Iotarphia Cameron (Coleoptera: Staphylinidae: Aleocharinae) with a description of new species based on morphological and molecular characters - Song, Jeong-Hun; Osborn, Andrew W.; Ahn, Kee-Jeong (Zootaxa, 2021)
A taxonomic review of the marine littoral genus Iotarphia Cameron is presented. Three species are recognized, one of which is described as a new species (I. magna Song & Ahn, sp. n.) based on morphological and molecular characters. Genetic divergence of COI using uncorrected p-distance among Iotarphia species ranged from 10% to 11.6%, while intraspecific divergence ranged from 0% to 1.3%. All three species were strongly supported as a single lineage on both neighbor-joining and parsimony trees. The genus Iotarphia and I. australis Cameron are redescribed with illustrations of diagnostic characters. The female of I. rufobrunnea is characterized for the first time. A key and comparison table for similarities and differences among the species are presented.